PENGARUH PELATIHAN, KOMPENSASI DAN KECERDASAN EMOSIONAL TERHADAP KINERJA GURU DI SMA NEGERI 1 SIPISPIS - Mira Mustika; Delita Sihotang; Dahliana Siregar; Marhamah Manurung; Irna Deviani Siregar (Jurnal Prodi Fakultas Ekonomi-UISU, 2022)
The formulation of the problem in this study are: How do training, compensation and emotional intelligence affect teacher performance. This study aims to determine how much influence training, compensation and emotional intelligence have on teacher performance. Sampling in this study using the Total Sampling technique, the sample in this study amounted to 33 people. The results of this study are; Partial training has a positive effect on teacher performance; Compensation partially has a positive effect on teacher performance; Emotional intelligence partially has a positive effect on teacher performance; Training, compensation and emotional intelligence have a positive effect on teacher performance.